The History of Extracorporeal Membrane Oxygenation and the Development of Extracorporeal Membrane Oxygenation Anticoagulation - Bartlett, Robert; Arachichilage, Deepa J.; Chitlur, Meera; Hui, Shiu-Ki Rocky; Neunert, Cindy; Doyle, Andrew; Retter, Andrew; Hunt, Beverley J.; Lim, Hoong Sern; Saini, Arun; Renné, Thomas; Kostousov, Vadim; Teruya, Jun (Seminars in Thrombosis and Hemostasis, 2023)
Extracorporeal membrane oxygenation (ECMO) was first started for humans in early 1970s by Robert Bartlett. Since its inception, there have been numerous challenges with extracorporeal circulation, such as coagulation and platelet activation, followed by consumption of coagulation factors and platelets, and biocompatibility of tubing, pump, and oxygenator. Unfractionated heparin (heparin hereafter) has historically been the defacto anticoagulant until recently. Also, coagulation monitoring was mainly based on bedside activated clotting time and activated partial thromboplastin time. In the past 50 years, the technology of ECMO has advanced tremendously, and thus, the survival rate has improved significantly. The indication for ECMO has also expanded. Among these are clinical conditions such as postcardiopulmonary bypass, sepsis, ECMO cardiopulmonary resuscitation, and even severe coronavirus disease 2019 (COVID-19). Not surprisingly, the number of ECMO cases has increased according to the Extracorporeal Life Support Organization Registry and prolonged ECMO support has become more prevalent. It is not uncommon for patients with COVID-19 to be on ECMO support for more than 1 year until recovery or lung transplant. With that being said, complications of bleeding, thrombosis, clot formation in the circuit, and intravascular hemolysis still remain and continue to be major challenges. Here, several clinical ECMO experts, including the “Father of ECMO”—Dr. Robert Bartlett, describe the history and advances of ECMO.
Keywords: ECMO; History; Anticoagulation